Pengembangan Metode Demonstrasi pada Pembelajaran PAI Untuk Anak Disabilitas di SLBN Pandaan - Pranesti Dini Afiarohma; Askhabul Kirom; Ahmad Ma’ruf (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to develop demonstration methods in the teaching of Islamic Religion Education for children with disabilities at the State Extraordinary School of Pandaan. The demonstration method is chosen for its ability to convey material visually and practically, which can enhance the understanding and involvement of students with special needs. This research uses qualitative research. Data collection is done through observations, interviews, and documentation. The results of the study show that the demonstration method is effective in improving understanding of the basic concepts of PAI among students with various types of disabilities, such as tunarung and tunagrahita. The application of this method also contributes positively to the learning motivation and active involvement of students in the learning process. Based on these findings, it is suggested that demonstration methods be more widely integrated into the curriculum of Islamic Religious Education at the State Extraordinary School of Pandaan and other extraordinary schools, with suitable adaptations to meet the individual needs of students.